Regards croisés, regards intéressés - Roberto Ceamanos Llorens (Mélanges de la Casa de Velázquez, 2011)
The PCF developed a discourse on the Spanish Second Republic that was tendentious and plagued with forced historical references. However, we should not forget that the communist press was the main source of information for a major portion of the French population, which was indoctrinated with a language that was simple and black-and-white but was also direct and forceful, addressing the problems that most affected France between the wars. This discourse utilised news from Spain in favour of the interests of French and International Communism and reveals the spectacular change in Communist strategy following the formation of the popular fronts. The initial goal of bringing down the Republic was replaced by a stout defence of republican legitimacy born of a conviction that if the Spanish Republic fell, this would endanger the future of the French Republic itself, and ultimately also the Soviet Union.